Emotional Intelligence Among B.Sc. Nursing Students In Selected Nursing Colleges Of Surat City (The Review of Diabetic Studies, 2025)
Background: Emotional intelligence (EI) — the capacity to recognize, understand and manage one’s own and others’ emotions — is important for nursing students’ personal development and professional functioning.Objectives: To assess the level of emotional intelligence among B.Sc. Nursing students in selected nursing colleges of Surat city and to determine the association between EI and selected demographic variables.Methodology:A quantitative research approach with a descriptive research design was employed to assess the variables under study. The research was conducted among 3rd-year B.Sc. Nursing students in selected nursing colleges of Surat, namely Government College of Nursing, T & T.V. Institute of Nursing, and Kiran College of Nursing. The target population consisted of students enrolled in these institutions. A total of 60 samples were selected using a non-probability purposive sampling technique after obtaining informed consent. Data were collected in the natural classroom setting using structured tools, and both descriptive and inferential statistics were applied for analysis.Results:Most students (75.0%) had high emotional intelligence, 20.0% had average levels, and 5.0% had low levels. Significant associations were observed between EI and age (p = 0.0056), gender (p = 0.0187), type of family (p = 0.0396), and family income (p = 0.0493). No significant association was found with religion, parents’ education and area of residence.Conclusions: The majority of nursing students showed high emotional intelligence. Age, gender, family type and family income were significantly associated with EI. Incorporating EI development in nursing curricula and student-support programs may further enhance students’ emotional competencies and future professional performance.